Photoinduced cytotoxic effect of fullerenes C60 on transformed T-lymphocytes - Prylutska, S.V.; Grynyuk, I.I.; Palyvoda, K.O.; Matyshevska, O.P. (Experimental Oncology, 2010)
Aim: To estimate the viability of normal and transformed T-lymphocytes after UV/Vis irradiation in the presence of pristine fullerenes C60. Methods: Thymocytes were isolated from Wistar rats’ thymus. Murine leukemia L1210 and human lymphoma Jurkat cells were used in this study. Mercury-vapor lamp was used for fullerenes C60 photoexcitation. Cytotoxicity was etermined by MTT assay. Changes in cell morphology were monitored by phase-contrast light microscopy. Results: fullerenes C60 exhibit cytotoxic effect against transformed T-lymphocytes when combined with UV/Vis irradiation (320–600 nm). Photoinduced effect was enhanced with the increasing of irradiation time period and C60 concentration, cell death was registered after 24 hours incubation. Fullerenes C60 photocytotoxicity against normal T-lymphocytes (thymocytes) was not observed. Conclusion: The present study suggests that pristine fullerenes C60 have the potential to be an effective photosensitizer and exhibit cytotoxic effect on transformed T-cells in vitro.